Methemoglobinemia in a Newborn - Shakya, Shristi; Shrestha, Nisha Jyoti; Subedi, Kalpana Upadhaya (Medical Journal of Shree Birendra Hospital, 2020)
Methaemoglobinaemia in a new born is a rare cause of cyanosis. We report a case of a new born presented with cyanosis and with normal cardio-pulmonary system. He was diagnosed as methemoglobinemia due to persistent cyanosis despite administration of oxygen and arterial blood gas collection appeared chocolate brown in colour. As methaemoglobin report was in mild range (11.7%), he was treated symptomatically.